Centro de recreación flexible con arquitectura contemporánea en el cantón Las Lajas- El Oro - Morocho Ordoñez, Edwin Joel (2024)
The project proposes a Flexible Recreation Center with Contemporary Architecture for the canton of Las Lajas, taking into account urban expansion and the need for public infrastructure that can meet both current and future demand. The design provides functional and recreational spaces, facilitating an improvement in the quality of life, all of which is achieved through the use of current regulations, urban design and architecture. Its design is made up of green spaces, resting areas, commercial spaces, sports, leisure and urban furniture......